The Cognitive Reflection Test as a predictor of performance on heuristics-and-biases tasks - Toplak, Maggie E.; West, Richard F.; Stanovich, Keith E. (Memory & cognition, 2011)
The Cognitive Reflection Test (CRT; Frederick, 2005 ) is designed to measure the tendency to override a prepotent response alternative that is incorrect and to engage in further reflection that leads to the correct response. In this study, we showed that the CRT is a more potent predictor of performance on a wide sample of tasks from the heuristics-and-biases literature than measures of cognitive ability, thinking dispositions, and executive functioning. Although the CRT has a substantial correlation with cognitive ability, a series of regression analyses indicated that the CRT was a unique predictor of performance on heuristics-and-biases tasks. It accounted for substantial additional variance after the other measures of individual differences had been statistically controlled. We conjecture that this is because neither intelligence tests nor measures of executive functioning assess the tendency toward miserly processing in the way that the CRT does. We argue that the CRT is a particularly potent measure of the tendency toward miserly processing because it is a performance measure rather than a self-report measure.